Sosialisasi Penerapan Listrik Kerakyatan Untuk Mengatasi Masalah Kebutuhan Energi Listrik Di Pedesaan - Arief Suardi Nur Chairat; Jasmid Edy; Vendy Antono; Nofirman Nofirman; Michiel Martin Rumondor (Sekolah Tinggi Teknik - PLN, 2019)
Rokan Hulu is one of the regencies in Riau Province which has an area of ​​about 7747.01 km2 which is divided into 16 (sixteen) districts. One of the problems with the environment is the increase in garbage in the Final Processing Site (TPA) which raises the problem of limited landfill land and the cost of processing waste in the landfill is getting bigger. The waste landfill in Rokan Hulu Regency is located in Tanjung belit Village which has an area of ​​± 2.5 Ha and is 5 km from the residential area. The waste disposed of in this landfill reaches 10-13 (ten to thirteen) tons per day. Until now the collection of sanded waste collection can not be realized effectively due to lack of public awareness of the cleanliness of the environment and on the other hand the location or area of ​​the landfill that is far from Pasir Pengaraian City, and the road or access to the landfill site is still inadequate, besides the limited transportation equipment in the transportation of waste provided by the Environment Agency.